2023
DOI: 10.1111/pce.14596
|View full text |Cite
|
Sign up to set email alerts
|

The integration of reactive oxygen species (ROS) and calcium signalling in abiotic stress responses

Abstract: Reactive oxygen species (ROS) and calcium (Ca2+) signalling are interconnected in the perception and transmission of environmental signals that control plant growth, development and defence. The concept that systemically propagating Ca2+ and ROS waves function together with electric signals in directional cell‐to‐cell systemic signalling and even plant‐to‐plant communication, is now firmly imbedded in the literature. However, relatively few mechanistic details are available regarding the management of ROS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 203 publications
0
10
0
Order By: Relevance
“…Furthermore, for MU_treat, the genes encoding calcium-dependent protein kinases (CDPKs) and respiratory burst oxidase homologues (RBOHs) were mostly up-regulated (Supplementary Figure S3). As reported, CDPKs and RBOHs were both central factors for plants in triggering ROS release in biotic stress responses and were mainly regulated through calcium signaling [37,38], so we speculated that P. canadensis might proceed along a similar pathway to produce ROS in response to MU penetration.…”
Section: Discussionmentioning
confidence: 77%
“…Furthermore, for MU_treat, the genes encoding calcium-dependent protein kinases (CDPKs) and respiratory burst oxidase homologues (RBOHs) were mostly up-regulated (Supplementary Figure S3). As reported, CDPKs and RBOHs were both central factors for plants in triggering ROS release in biotic stress responses and were mainly regulated through calcium signaling [37,38], so we speculated that P. canadensis might proceed along a similar pathway to produce ROS in response to MU penetration.…”
Section: Discussionmentioning
confidence: 77%
“…As mentioned, the most promising molecular candidate functioning as a second messenger of SW is Ca 2+ . There are interconnections between ROS and Ca 2+ signaling in the perception and transmission of environmental signals in plants [ 64 ]. It has been shown that the activities of certain ROS-generating enzymes are regulated directly or indirectly by the concentration of Ca 2+ [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…All plants adopt nonspeci c strategies, depending on the stress and duration. However, the general mechanism produces ROS and activates the antioxidant defense system [40]. The ROS acts as a signaling molecule that initiates several metabolic processes in plants to combat stress, such as the production of phytohormones, secondary metabolites, activation of some genes and modulation in physio-biochemical processes.…”
Section: Discussionmentioning
confidence: 99%